Coenzyme Q deficiency causes impairment of the sulfide oxidation pathway - Marcello Ziosi; Ivano Di Meo; Giulio Kleiner; Xing‐Huang Gao; Emanuele Barca; Maria J Sanchez‐Quintero; Saba Tadesse; Hongfeng Jiang; Changhong Qiao; Richard J Rodenburg; Emmanuel Scalais; Markus Schuelke; et al. (EMBO Molecular Medicine)
Abstract Coenzyme Q (CoQ) is an electron acceptor for sulfide‐quinone reductase (SQR), the first enzyme of the hydrogen sulfide oxidation pathway. Here, we show that lack of CoQ in human skin fibroblasts causes impairment of hydrogen sulfide oxidation, proportional to the residual levels of CoQ. Biochemical and molecular abnormalities are rescued by CoQ supplementation in vitro and recapitulated by pharmacological inhibition of CoQ biosynthesis in skin fibroblasts and ADCK3 depletion in HeLa cells. Kidneys of Pdss2kd/kd mice, which only have ~15% residual CoQ concentrations and are clinically affected, showed (i) reduced protein levels of SQR and downstream enzymes, (ii) accumulation of hydrogen sulfides, and (iii) glutathione depletion. These abnormalities were not present in brain, which maintains ~30% residual CoQ and is clinically unaffected. In Pdss2kd/kd mice, we also observed low levels of plasma and urine thiosulfate and increased blood C4‐C6 acylcarnitines. We propose that impairment of the sulfide oxidation pathway induced by decreased levels of CoQ causes accumulation of sulfides and consequent inhibition of short‐chain acyl‐CoA dehydrogenase and glutathione depletion, which contributes to increased oxidative stress and kidney failure.